Sistem Pendukung Keputusan Pemberian Bantuan Pemasangan PDAM Gratis Di Kabupaten Kepahiang - Saputra, Reza; Siswanto, Siswanto; Suranti, Dewi (Jurnal Media Infotama, 2024)
The increasingly difficult economic conditions make the government have to play a greater role in the problem of poverty. With this free PDAM installation assistance, it is hoped that it can ease the burden on poor people who experience water difficulties. But often the provision of free PDAM installation assistance for low-income communities is still not right on target. Therefore, the author took the initiative to make a decision support system for providing free PDAM installation assistance for low-income people. The method used in this decision support system is the SAW method used to assess or select several alternatives in a limited number. The output results of this system are in the form of a ranking of community recommendations for recipients of free PDAM installation assistance which are assessed based on occupation, income, house conditions, and number of family dependents. Based on the test results of 14 samples of prospective beneficiaries in one village processed using the SAW method, the results obtained are prospective beneficiaries with the 3rd best Vi rating, because in one village only 3 beneficiaries received assistance